Inclusion of Deaf and Hard of Hearing Students In Universities: Experience of United Kingdom - Ungeitytė, Indrė; Alisauskiene, Stefanija (Special Education, 2022)
This research project has been conducted in United Kingdom and in total 10 respondents have been questioned from 3 different universities based in London. The aim of the research was to reveal the possibilities of deaf and hard of hearing students to be included into university studies. The main objectives of the research are: to analyse the accessibility to universities for deaf and hard of hearing students; to enquire about the availability of necessary tools and equipment for inclusion and how disabilities caused by hearing loss are offset or compensated for; to investigate how the curriculum is adapted to meet the additional learning needs of such students. The nature of participants has been university additional learning support staff and teaching staff members (educators). The qualitative approach has been applied for the research. The data has been collected by using online questionnaire, including spaces for comments. The data was analysed using thematic analysis as well as a compilation of the numerical results. The main conclusion of the research is: deaf and hard of hearing students often face difficulties while studying at universities because institutions are not fully accessible to such learners due to lack of resources and other necessary tools and equipment which could be used while learning. Lecturers are unable to provide all additional support to vulnerable students by themselves, educators need more training and support from their workplace. Curriculum remains the same for all students but sometimes there might be exceptions related with time. Usually deaf and hard of hearing student can have more time to complete given tasks.